PENGARUH KREATIVITAS, INOVASI DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA PADA UMKM - Fatmasari - Fatmasari; Andi Irmayana (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to analyze (1) the effect of creativity on the business success of MSME actors, (2) the influence of innovation on the business success of MSME actors, (3) the effect of entrepreneurial knowledge on the business success of MSME actors and (4) the influence of creativity, innovation and entrepreneurial knowledge on simultaneously to the business success of MSME actors. This research method uses descriptive and verification methods by distributing questionnaires to MSME actors assisted by PT. Energi Bayu Jeneponto with 40 respondents and using multiple linear regression analysis. The results of the study show that (1) creativity has no significant effect on the success of MSME actors' businesses (2) innovation has no significant effect on MSME business success; (3) Entrepreneurial knowledge has a positive and significant effect on the business success of MSME actors. (4) Creativity, product innovation and entrepreneurial knowledge have a positive and significant simultaneous effect on the business success of MSME players. That is, if creativity, product innovation and entrepreneurial knowledge are increased together it will have an impact on increasing business success and vice versa if creativity, product innovation and entrepreneurial knowledge decrease together it will result in a decrease in business success